College admissions with entrance exams: Centralized versus decentralized - Isa E. Hafalir; Rustamdjan Hakimov; Dorothea Kübler; Morimitsu Kurino (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
We theoretically and experimentally study a college admissions problem in which colleges accept students by ranking students' efforts in entrance exams. Students hold private information regarding their ability level that affects the cost of their efforts. We assume that student preferences are homogeneous over colleges. By modeling college admissions as contests, we solve and compare the equilibria of "centralized college admissions" (CCA) in which students apply to all colleges, and "decentralized college admissions" (DCA) in which students can only apply to one college. We show that lower ability students prefer DCA whereas higher ability students prefer CCA. The main qualitative predictions of the theory are supported by the experimental data, yet we find a number of behavioral differences between the mechanisms that render DCA less attractive than CCA compared to the equilibrium benchmark.
Keywords: C78; D47; D78; I21; 330; college admissions; incomplete information; student welfare; contests; all-pay auctions; experiment